The Impact of Political Marketing Mix on Repeated Voting Decision in Indonesian General Elections: A Case Study of FEB Universitas Riau Students - Alvi Furwanti Alwie; Rendra Wasnury; Jushermi Jushermi; Nia Anggraini; Monica Agnes Br Harianja; Dedi Hidayat (Eduvest - Journal of Universal Studies, 2023)
Politics is the basic policy of the state administration that is currently and will apply, which is sourced from the values ​​that apply in society to achieve state goals. The purpose of government-run politics is to achieve the welfare of the general public. Elections are a form of political participation as an embodiment of people's sovereignty, because at the time of voting, the people become the most decisive party for the political process in an area by voting directly. This study aims to determine whether the influence of the Political Marketing Mix on the decision to choose repeat voters in General Elections in Indonesia (a case study on FEB students, Universitas Riau). This study applied quantitative research method. The analysis technique used is multiple linear regression with the test equipment using Warp PLS 7.0. The number of samples to be taken as many as 145 respondents with purposive sampling method. The data was collected by distributing online questionnaires. Based on the results of the study, it was found that: 1) Political products have a significant effect on voting decisions. 2) Political Promotion has a significant effect on the Decision to Choose. 3) Political Price has a significant effect on the Decision to Choose. 4) Political distribution has a significant effect on voting decisions